HANSENS AND SUMMERS HYPOTHESIS OF SECULAR STAGNATION IN MACROECONOMICS - Veljković, Marija (Ekonomija - teorija i praksa, 2022)
At a times when the world’s most developed and those less developed economies are recording historically weak levels of economic performance after the Great Recession of 2008, when the world is facing decades of low demographic growth, in the frames of macroeconomic theory Summers revives the discussion about Hansen’s once-debated and forgotten "old" secular stagnation hypothesis through a "new" secular stagnation hypothesis. Consequently, the subject of research in this paper are Hansen’s "old" and Summers’ "new" secular stagnation hypotheses, which together belong to Keynesian theories of stagnation and are based on the demand-side causes. The aim of this paper is to analyze, present and explain the key determinants of the observed instances in macroeconomic theory, trying to contribute to contemporary economic theory in terms of a critical analysis of the secular stagnation hypothesis of the two most important theoretical points of view in the macroeconomic thought.